Maternal obesity and dyslipidemia associated with gestational diabetes mellitus (GDM). (March 2020) - O'Malley, Eimer G.; Reynolds, Ciara M.E.; Killalea, Anne; O'Kelly, Ruth; Sheehan, Sharon R.; Turner, Michael J.
Abstract: Objective: The association between gestational diabetes mellitus (GDM) and maternal dyslipidemia is well established, however, the role of obesity in this relationship is not well defined. We examined the relationship between maternal obesity at the first prenatal visit and fasting lipids measured at the time of the oral glucose tolerance test (OGTT) in women screened selectively for GDM. Study Design: This prospective observational study was conducted in a large university maternity hospital. Women were recruited at the first prenatal visit following measurement of their weight and height. Clinical and sociodemographic details were recorded. Women with maternal risk factors for GDM were screened selectively with a one-step 75 g OGTT at 26–28 weeks gestation. GDM was diagnosed based on the World Health Organization (WHO) 2013 criteria. Fasting lipids were measured simultaneously. Maternal lipid levels and their relationship with GDM and obesity were analysed with linear and logistic models. Results: Of the 275 women recruited at the first antenatal visit 202 attended for their OGTT at 26–28 weeks' and 53.5 % (108) had GDM based on the WHO criteria. The women with GDM were more likely to have obesity (70.4 % vs. 42.6 %, P < 0.001). Compared with women with a normal OGTT (n=94), women with GDM had higher triglycerides (P=0.023) and a lower HDL-Cholesterol ( P = 0.013). However, when the cohort with GDM were stratified according to obesity, this trend was only seen in the women who had a BMI >29.9kg/m 2 . Based on tertiles, women with GDM had a higher odds ratio of increased triglycerides (odds ratio 3.2 (95 % confidence interval; 1.4–6.9), P = 0.004) and lower HDL-Cholesterol (odds ratio 2.2, (95 % confidence interval; 1.1–4.7), P = 0.036) and an increased TG:HDL-cholesterol ratio (odds ratio 2.3, (95 % confidence interval; 1.1–4.9), P = 0.026), only if they had obesity. Conclusion: Our findings suggest that the epidemiological association between GDM and dyslipidemia is mediated through maternal obesity. Women with obesity alone or GDM alone did not have an elevated OR for dyslipidemia. Interventions designed to optimise maternal lipids should prioritise women with obesity and it may be preferable for these interventions to start prior to conception.